Pengaruh Kepuasan Kerja Dan Komunikasi Terhadap Kinerja Pegawai Pada Dinas Pendidikan Provinsi DKI Jakarta - Delvia, Della; Guruh, Muhamad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the effect of job satisfaction and communication on employee performance at the DKI Jakarta Provincial Education Office. The method used is descriptive quantitative with an associative approach. The sampling technique uses non-probability sampling with convenience sampling using the Slovin formula with a sample size of 67 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient, and hypothesis testing. The results of this study show that job satisfaction has a significant effect on employee performance with a coefficient of determination of 26.1% and a hypothesis test obtained a t-value > t-table or (4.790 > 1.997). Communication has a significant effect on Employee Performance with a coefficient of determination of 24.8% and a hypothesis test obtained a t-value > t-table or (4.628 > 1.997). Job satisfaction and communication simultaneously have a significant effect on employee performance with the regression equation Y = 5.079 + 0.545 X1 + 0.403 X2. The coefficient of determination is 69.6%, while the remaining 30.40% is influenced by other factors. The hypothesis test obtained a value of F count > F table or (30.020 > 3.140).